A country-wide teledermatoscopy service in Estonia shows results comparable to those in experimental settings in management plan development and diagnostic accuracy: A retrospective database studyCapsule Summary - Christian Koop, MD; Priit Kruus, MSc; Riina Hallik, MSc, MMS, RN; Hannes Lehemets, MSc; Elen Vettus, MD; Marianne Niin, MD, PhD; Peeter Ross, MD, PhD; Külli Kingo, MD, PhD (Elsevier, 2023)
Background: Teledermatoscopy accuracy has been examined in experimental settings and is recommended for primary care despite lacking real-world implementation evidence. A teledermatoscopy service has been provided in Estonia since 2013, where lesions are evaluated based on the patient's or general practitioner's suggestion. Objective: The management plan and diagnostic accuracy of a real-world store-and-forward teledermatoscopy service for melanoma diagnosis were evaluated. Methods: A retrospective study analyzed 4748 cases from 3403 patients using the service between October 16, 2017 and August 30, 2019 by matching country-wide databases. Management plan accuracy was calculated as the percentage of melanoma found that was managed correctly. Diagnostic accuracy parameters were sensitivity, specificity, and positive and negative predictive values. Results: Management plan accuracy for melanoma detection was 95.5% (95% CI, 77.2-99.9). Diagnostic accuracy showed a sensitivity of 90.48% (95% CI, 69.62-98.83) and a specificity of 92.57% (95% CI, 91.79-93.31). Limitations: Matching the lesions was limited to SNOMED CT location standard precision. Diagnostic accuracy was calculated based on a combination of diagnosis and management plan data. Conclusion: Teledermatoscopy for detecting and managing melanoma in real-world clinical practice displays results comparable with those in experimental setting studies.